Driving factors of parental vaccine hesitancy towards COVID-19 vaccines for children in Petaling District, Malaysia - Minhat, Halimatus Sakdiah; Lim, Poh Ying (Malaysian Public Health Physicians Association, 2024)
Parental vaccine hesitancy (PVH) is a crucial barrier towards effective public health intervention, which refers to a delay in accepting or refusing vaccines despite its availability. This research seeks to determine the prevalence and driving factors of PVH against the COVID-19 vaccination for children in the Petaling district, guided by the the Health Belief Model and Theory of Planned Behavior. Parents of pre-school children in the Petaling district were recruited using a stratified proportionate-to-size random sampling method. A validated and reliable self-administered questionnaire was used, and three-level data analysis was done using SPSS Version 27.0. A PVH prevalence of 64.4% was obtained, in which 34.1% delayed and 30.3% refused vaccination. Parents with a high perceived barrier to taking the COVID-19 vaccination were 3.26 times more likely to be vaccine-hesitant (aOR=3.259, 95% CI: 1.994,5.324). Inversely, parents who have high perceived susceptibility, high subjective norms, and high cues to action had lower odds of being vaccine-hesitant respectively (aOR=0.286, 95% CI: 0.160,0.509, p<0.001; aOR=0.391, 95% CI: 0.211,0.723, p=0.003; aOR=0.331, 95% CI: 0.181,0.607, p<0.001). Also, parents aged more than 35 years old have 0.4 lesser odds of being vaccine-hesitant than parents aged less than 30 years old of age (aOR=0.419, 95% CI: 0.186,0.943, p=0.035). The high prevalence of parental vaccine hesitancy necessitating a nuanced strategy that considers each parent's specific concerns and beliefs related to the vaccination program.